2003
DOI: 10.1002/jhet.5570400517
|View full text |Cite
|
Sign up to set email alerts
|

Relative ortho‐directing power of fluorine, chlorine and methoxy group for the metalation reaction in the diazine series. Diazines XXXV

Abstract: The regioselectivity of the metalation of 2‐chloro‐6‐methoxypyrazine, 2‐fluoro‐6‐methoxypyrazine and 3‐fluoro‐6‐chloropyridazine was studied; the relative ortho‐directing power was F > OMe > Cl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…With 3-chloro-6fluoropyridazine, metalation using either LDA or LTMP in 65 THF at low temperature took place next to the smaller halogen. 22 With a pivaloylamino group instead, reaction using LTMP in THF at -70 °C occurred randomly whereas employing LDA (4 equiv.) exclusively afforded deprotonation at the position adjacent to the halogen, providing after 70 trapping with acetaldehyde or benzaldehyde the expected alcohols in 68-82% yields.…”
Section: Metalation Of Pyridazines Cinnolines and Phthalazines 21 Mmentioning
confidence: 99%
See 2 more Smart Citations
“…With 3-chloro-6fluoropyridazine, metalation using either LDA or LTMP in 65 THF at low temperature took place next to the smaller halogen. 22 With a pivaloylamino group instead, reaction using LTMP in THF at -70 °C occurred randomly whereas employing LDA (4 equiv.) exclusively afforded deprotonation at the position adjacent to the halogen, providing after 70 trapping with acetaldehyde or benzaldehyde the expected alcohols in 68-82% yields.…”
Section: Metalation Of Pyridazines Cinnolines and Phthalazines 21 Mmentioning
confidence: 99%
“…55b,c Recourse to 30 very hindered base lithium N-tert-butyl-N-(1isopropylpentyl)amide (LB 1 ) lowered the regioselectivity at the position adjacent to the methoxy group. 22 Replacing the chloro group with an iodo resulted in a complete regioselectivity when LDA was used in THF at -70 °C. 55b 35 When 2-fluoro-6-methoxypyrazine was allowed to react with LDA in THF at -70 °C for 5 min, trapping with aldehydes showed deprotonation mainly occurred next to the fluoro group (96:4 ratio); LTMP and N-tert-butyl-N-(1isopropylpentyl)amide (LB 1 ) gave lower selectivities.…”
Section: Metalation Of Halo-pyrazines and Quinoxalinesmentioning
confidence: 99%
See 1 more Smart Citation
“…With the requisite 4,6-disubstituted indazoles in hand, our attention turned to the regioselective C–H functionalization of the C5-position. Although 1 H NMR analysis indicated that the C7-proton is likely most acidic, we speculated that the C4-fluorine could serve as a directing group to achieve deprotonation at the C5-position. Quenching the anion with an electrophilic chlorinating agent would provide desired indazole 3c .…”
mentioning
confidence: 99%
“…A number of schemes for the preparation of the cycloheptenone 9 could be envisaged, one of which involves an intramolecular Heck reaction of the halopyrazine 11 . It seemed likely that the haloindole substituent would tolerate this transformation based on the well-precedented superior reactivity of pyrazinyl halides toward oxidative addition. 4e-h Finally, the pyrazine 11 could be assembled by addition of the appropriate metalated pyrazine to the readily available, optically pure aldehyde 12 2 …”
mentioning
confidence: 99%